A certain investigations on the performance issues of smart antennas for cellular mobile communications - Gunasekaran, T.; Shankar Kumar, K.R.; Manisankar, S.; Parthiban, K.; Periyasamy, I.; Sivakumar, R. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.